THEORETICAL ASPECTS OF MONETARY AND FISCAL POLICY COORDINATION AS A NECESSARY CONDITION FOR ENSURING MACROFINANCIAL STABILITY - DZIUBLIUK, Oleksandr (Scientific journal «World of Finance», 2024)
Introduction. Monetary and fiscal policy are the main levers of the state's influence on the economy when prompt response to a crisis caused by internal or external shocks is required. This determines the importance of theoretical substantiation of the main aspects of coordination of monetary and fiscal regulation, when the coordinated work of key state institutions is important.The purpose of the article is to clarificate the main theoretical aspects and practical mechanisms of implementing the monetary and fiscal policy of the state through the prism of interaction and coordination of the impact on the economy.Results. The role of monetary and fiscal regulation as the main directions of state influence on the economy is outlined. The modern financial theories are analyzed, which indicates serious attention paid to the coordination of fiscal and monetary policy. Monetary and fiscal regulation are considered as two components of the institutional mechanism for ensuring macrofinancial stabilization. Factors of institutional interdependence of state institutions in the process of implementing fiscal and monetary policy are systematized. Four main scenarios of combination of monetary and fiscal policy measures are defined, which determines the restrictive or expansionary nature of the impact on the economy. Factors of coordination between fiscal and monetary policy methods are considered. The elements of the technical organization of the interaction of monetary and fiscal policy, which require practical filling of the mechanism of state regulation, are substantiated.Perspectives. An important direction of scientific research for the future is the search for ways to optimize the mechanism of interaction at the institutional level of monetary and fiscal policy in the system of state regulation of the economy.